O uso de técnicas de testes com usuário combinadas com visualização de dados para aperfeiçoar um jogo masocore de plataforma 2D - Bastos, Arthur Silva (2021)
As the video game industry evolves, creating games for more diverse and demanding players becomes an increasingly complex task. Modern developers apply methods of Games User Research (GUR) to make better informed decisions based on the target audience. Traditional methods include observation, interview and questionnaire. To obtain detailed information about users, complementary methods may be required. This thesis analyzes the inclusion of two complementary low-cost methods, namely webcam-based eye-tracking and telemetry, combined with the data visualization, in a testing routine. The data acquired by these methods were visualized using a tool customized according to the needs of the project, which was duly tested by professionals and students in the field. The development of three versions of a 2D hardcore platform game whose differential lies in its multitasking mechanics showed, through the comparison of the prototypes, that the chosen complementary methods highlighted a significant part of the gameplay issues encountered. Analysis of the tool showed that the data derived from metrics and eye-tracking provided insight into multitasking and level design. Finally, the work discusses the challenges in evaluating prototypes under the criterion of the pleasantness of the experience when frustration is a desirable gameplay element.